Bioinformatics and Biosimulations as Toolbox for Peptides and Peptidomimetics Design: Where Are We? - D’Annessa, Ilda; Di Leva, Francesco Saverio; La Teana, Anna; Novellino, Ettore; Limongelli, Vittorio; Di Marino, Daniele (Frontiers in Molecular Biosciences, 2020)
Peptides and peptidomimetics are strongly re-emerging as amenable candidates in the development of therapeutic strategies against a plethora of pathologies. In particular, these molecules are extremely suitable to treat diseases in which a major role is played by protein-protein interactions (PPIs). Unlike small organic compounds, peptides display both a high degree of specificity avoiding secondary off-targets effects and a relatively low degree of toxicity. Further advantages are provided by the possibility to easily conjugate peptides to functionalized nanoparticles, so improving their delivery and cellular uptake. In many cases, such molecules need to assume a specific tridimensional conformation that resembles the bioactive one of the endogenous ligand. To this end, chemical modifications are introduced in the polypeptide chain to constrain it in a well-defined conformation, and to improve its drug-like characteristics. In this context, a successful strategy for peptide/peptidomimetics design and optimization is to combine different computational approaches ranging from structural bioinformatics to atomistic simulations. Here, we review the state-of-the-art bioinformatics tools for peptide design, highlighting their main features and differences, and discuss the computational protocols used to assess and improve the stability of the functional folding of the peptides. Finally, we introduce the use of biosimulations to predict the binding affinity of the designed peptides for their targets.